Perubahan Metodologi Kritik Matan Hadis - Bustamin Bustamin (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2003)
The critique of hadith matn is relatively rare among muhaddithin compared to their efforts in hadith isnad critique. This is not without reason, as they believe a hadith of the Prophet cannot be considered authentic without a chain of transmission connecting it back to the source, the Prophet Muhammad (PBUH). A well-phrased statement that aligns with Islamic teachings cannot be regarded as a hadith if the chain of narrators linking it to the Prophet is not found. Conversely, a sound isnad has no value if the matn cannot be substantiated. This paper aims to elaborate on the evolving methodology in the critique of hadith matn. This study will discuss various aspects underlying this evolution, including the crucial role of matn critique in ensuring the integrity and authenticity of hadith. Through a historical approach and critical analysis, the research will explore how scholars have developed new methods to assess the validity of hadith matn and the implications of these approaches on hadith sciences as a whole. Additionally, the paper will identify the challenges faced in the application of matn critique, such as overcoming subjective biases and maintaining a balance between isnad and matn critique. By examining the views of both classical and contemporary scholars, this research will provide a comprehensive overview of the evolution of matn critique methodology and its relevance in the modern context. This study aims to offer deep insights into the importance of hadith matn critique and encourage further research in this field, thereby enriching Islamic scholarship and strengthening the understanding of the hadiths of the Prophet Muhammad (PBUH).